The Influence of Technological Determinism through Social Media on Farmers' Adoption of Agricultural Innovations - Mariewentty Clarmel Ruhunlela; Mariko Rizkiansyah (Research Synergy Foundation Press, 2025)
The agricultural sector has entered the era of Industrial Revolution 4.0, marked by the integration of internet-based technologies such as IoT (Internet of Things) devices and precision farming tools into agricultural practices. This transition offers significant opportunities to enhance community creativity and engagement. This study focuses on Saparua Island in Central Maluku Regency, examining how farmers perceive technological determinism through social media and its impact on agricultural productivity. A qualitative approach was used, employing reception analysis with an encoding-decoding model. Twenty-five respondents were categorized into three positions: dominant, negotiated, and oppositional. The findings reveal diverse public responses to the program